A Laboratory Phenotype/Genotype Correlation of 1167 French Patients From 670 Families With von Willebrand Disease: A New Epidemiologic Picture. Issue 11 (March 2016) - Veyradier, Agnès; Boisseau, Pierre; Fressinaud, Edith; Caron, Claudine; Ternisien, Catherine; Giraud, Mathilde; Zawadzki, Christophe; Trossaert, Marc; Itzhar-Baïkian, Nathalie; Dreyfus, Marie; d'Oiron, Roseline; Borel-Derlon, Annie; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: von Willebrand disease (VWD) is a genetic bleeding disease due to a defect of von Willebrand factor (VWF), a glycoprotein crucial for platelet adhesion to the subendothelium after vascular injury. VWD include quantitative defects of VWF, either partial (type 1 with VWF levels <50 IU/dL) or virtually total (type 3 with undetectable VWF levels) and also qualitative defects of VWF (type 2 variants with discrepant antigenic and functional VWF levels). The most bleeding forms of VWD usually do not concern type 1 patients with the mildest VWF defects (VWF levels between 30 and 50 IU/dL). The French reference center for VWD performed a laboratory phenotypic and genotypic analysis in 1167 VWD patients (670 families) selected by their basic biologic phenotype: type 3, type 2, and type 1 with VWF levels <30 IU/dL. In these patients indeed, to achieve an accurate diagnosis of VWD type and subtype is crucial for the management (treatment and genetic counseling). A phenotype/genotype correlation was present in 99.3% of cases; 323 distinct VWF sequence variations (58% of novel) were identified (missense 67% versus truncating 33%). The distribution of VWD types was: 25% of type 1, 8% of type 3, 66% of type 2 (2A: 18%, 2B: 17%, 2M: 19%, 2N: 12%), and 1% of undetermined type. Type 1 VWD was related either to a defective synthesis/secretion or to an accelerated clearance of VWF. In type 3 VWD, bi-allelic mutations of VWF were found in almost all patients. In type 2A, the most frequent mechanism was a hyper-proteolysis of VWF. Type 2B showed 85% of patients with deleterious mutations (distinct from type 2B New York). Type 2M was linked to a defective binding of VWF to platelet glycoprotein Ib or to collagen. Type 2N VWD included almost half type 2N/3. This biologic study emphasizes the complex mechanisms for both quantitative and qualitative VWF defects in VWD. In addition, this study provides a new epidemiologic picture of the most bleeding forms of VWD in which qualitative defects are predominant.